Assessment of the net effect of the active labour market policy in Bulgaria - Atanassov, Atanas (Array, 2020)
The assessment of the net effect of active labour market policy contributes to the effective use of public funds in order to achieve optimal results and provide opportunities for future changes in the priority areas of the employment action plans. The paper examines the basic concepts for assessing the net effect of active labour market policy and assesses the net effect of this policy in Bulgaria. In the process of assessing the impact of active labour market policy at the individual level for each program and measure included in the National Employment Action Plan in 2015 and funded from the state budget, the gross effect, deadweight effect, the substitution and displacement effects are estimated. The quasi-experimental design method is applied to assess the net effect of programs and measures on the labour market in Bulgaria. The estimation results demonstrate that the total net effect has the value of 14.5%. The net effect for women is significantly higher than for men. Regarding education, the highest net effect can be seen among those with primary or no education Regarding age, the highest net effect is observed among young people up to 24 years of age. As related to the duration of unemployment, the highest net effect can be seen among long-term unemployed people (over 24 months). In terms of working capacity, the highest net effect is observed among people with reduced working capacity. Regarding the type of settlement, the highest net effect can be seen in rural areas. The paper provides a number of conclusions and recommendations for increasing the effectiveness of active labour market policy and for improving the state of the labour market in Bulgaria. The analysis shows that in Bulgaria it is necessary to maintain the variety of different programs and measures on the labour market, covering different target groups.